2015
DOI: 10.1016/j.cjca.2015.07.469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Contact Force Technology on Atrial Fibrillation Ablation: A Meta-Analysis

Abstract: Background--Catheter-tissue contact is essential for effective lesion formation, thus there is growing usage of contact force (CF) technology in atrial fibrillation ablation. We conducted a meta-analysis to assess the impact of CF on clinical outcomes and procedural parameters in comparison to conventional catheter for atrial fibrillation ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The observations of shorter procedural times and lower radiation exposure with the use of CF‐sensing catheters have been consistent in published reports and are of importance for both the patients and operators. Data regarding outcomes have varied in the literature, but it has been suggested in meta‐analyses that CF‐sensing ablation catheters are associated with reduction in arrhythmia recurrence rates . However, it has been suggested that nonrobotic PersAF ablation with CF sensing was not associated with improved outcomes compared with traditional catheters .…”
Section: Discussionmentioning
confidence: 99%
“…The observations of shorter procedural times and lower radiation exposure with the use of CF‐sensing catheters have been consistent in published reports and are of importance for both the patients and operators. Data regarding outcomes have varied in the literature, but it has been suggested in meta‐analyses that CF‐sensing ablation catheters are associated with reduction in arrhythmia recurrence rates . However, it has been suggested that nonrobotic PersAF ablation with CF sensing was not associated with improved outcomes compared with traditional catheters .…”
Section: Discussionmentioning
confidence: 99%
“…There is now overwhelming proof that electrode–tissue contact force (CF) during RF application is a major determinant of RF lesions size . Using CF has been shown to decrease ablation, procedural time, and fluoroscopy time, but also to reduce clinical recurrences . A force time integral (FTI) between 392 and 404 gs and impedance drop at 8 or 10 ohms have been correlated transmurality obtention .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a meta‐analysis by Shurrab et al . comparing AF ablation outcomes using CFC or standard ablation catheters though did not show any statistical difference in major adverse events between groups (1.3% major complications in CF group versus 1.9% in control group; P = 0.45) …”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Contact-force catheters are technological breakthroughs. They increase the procedural efficacy (in other words less recurrences) and reduce fluoroscopy and procedure duration, 9 but their impact on safety outcomes remains controversial.…”
Section: Discussionmentioning
confidence: 99%